Diabetes mellitus HNF4A-MODY in children from the Russian population: clinical and genetic features - Sechko, Elena A.; Laptev, Dmitry N.; Koltakova, Mariia P.; Khusainova, Rita I.; Minniakhmetov, Ildar R.; Kuraeva, Tamara L.; Eremina, Irina A.; Titovich, Elena V.; Bezlepkina, Olga B.; Peterkova, Valentina A. (Frontiers in Endocrinology, 2025)
IntroductionHNF4A-MODY is a rare subtype of MODY in children that requires treatment. The clinical features of children with HNF4A-MODY are limited. Adult patients with HNF4A-MODY are treated with insulin, diet, oral antidiabetic drugs, and incretin drugs. Our cross-sectional study presents the clinical features of 15 probands with genetically confirmed HNF4A-MODY from the pediatric registry of MODY in Russia.Materials and methodsThis study presents the genetic, clinical, and laboratory characteristics of 15 children with HNF4A-MODY in the Russian population.ResultsThe frequency of HNF4A-MODY was 1.8%, 95% CI [1.0, 3.0] among all pediatric MODY cases (n = 15/807) in Russia. The median age at diagnosis was 12.8 years [12.1, 14.0]. Hyperglycemia was diagnosed incidentally in 71.5% of cases. Glycated hemoglobin (HbA1c) was 8.0% [7.0, 9.2]. At birth, macrosomia was present in 35.7% of patients and hypoglycemia in 7%. Family history was positive in 57.1%, with DM diagnosed in first-degree relatives at age 29 [27.3, 32.8] years in 50% of cases, which was significantly different from the age of DM diagnosis in their children (p < 0.05).DiscussionWe examined patients with HNF4A-MODY with a duration of 1.2 [0.8, 1.9] years. The degree of hyperglycemia in all patients met the diagnostic criteria for DM. Molecular genetic testing revealed a high percentage of deletions and nonsense variants (28.5% each). 64.5% of patients were prescribed drug therapy (21% insulin, 43% metformin) at the onset of diabetes. Forty-three percent of patients were transferred successfully to sulfonylurea therapy (including patients with complete insulin withdrawal) following genetic testing and HNF4A-MODY verification. The attempt to switch from insulin to sulfonylurea drugs was unsuccessful due to significant glycemic deterioration in one case.